2019
DOI: 10.1111/and.13388
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of intralesional verapamil injection in the treatment of Peyronie's disease today

Abstract: Studies assessing the efficacy of intralesional verapamil injection in the treatment of Peyronie's disease have yielded mixed results. The purpose of this meta‐analysis is to systematise the existing literature on the efficacy of intralesional verapamil injection when used in the treatment of Peyronie's disease. The treatment outcomes of seven different study groups identified by computerised literature search were compared with natural history outcomes and data from control groups of three studies involving p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The remaining 42 articles were selected as eligible for the present review. Tables 1 [21][22][23][24][25][26][27][28] and 2 [29][30][31][32][33][34][35] summarise the highest impact and most clinically relevant studies to our research topicTables 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 42 articles were selected as eligible for the present review. Tables 1 [21][22][23][24][25][26][27][28] and 2 [29][30][31][32][33][34][35] summarise the highest impact and most clinically relevant studies to our research topicTables 2.…”
Section: Resultsmentioning
confidence: 99%
“…In a subsequent, and more reputable study, he showed verapamil injection reduced pain in 97% of patients, improved sexual function in 72%, and lessened the degree of curvature and deformity in 54% and 86%, respectively [ 22 ]. But other studies have shown IL verapamil to improve sexual function while not having much effect on the size of fibrous plaque [ 23 ]. It is for these mixed results and a lack of large-scale placebo-controlled studies that the United States Food and Drug Administration (FDA) has not formally approved verapamil for the treatment of PD.…”
Section: Therapiesmentioning
confidence: 99%
“…While most of the published PD studies reported positive outcomes, many studies lack standardized outcome measures to allow for direct comparison [ 11 ]. Studies have shown that the volume and duration of the ILV protocol could play a role, too [ 1 2 3 4 ]. While the 6 courses of verapamil given in our study protocol were similar to Levine’s original study [ 4 ], the volume of injection was different (10 mL in Levine’s vs. 4 mL in our study).…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review of various intralesional plaque injectable agents have highlighted mixed clinical outcomes, and most of these agents are used as an off-label indication apart from collagenase Clostridium histolyticum (CCH) [ 1 3 ]. Intralesional verapamil (ILV) injection has been around for more than 3 decades and is shown to improve penile curvature and plaque volume [ 1 2 4 ]. The publication of 2 large-scale phase III clinical trials, Investigation for Maximal Peyronie’s Reduction Efficacy and Safety Studies (IMPRESS) I and II [ 5 ], has demonstrated that CCH significantly reduces penile curvature and plaque volume, and improves PD-associated symptom bother scores.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of seven different studies, intralesional injection of Verapamil significantly improved sexual function (p <0.0005) and penile curvature (p <0.005) in patients. There is an imprecise but significant reduction in pain after the treatment, but less effect on plaque size (p> .05) (65). In a prospective, single-blind, randomized study, the use of Verapamil in Peyronie's disease showed improvement in penile curvature and reduction in plaque size (66).…”
Section: Evidencementioning
confidence: 99%